Quantitative Evaluation of Changes in the Clock-Watching Behavior of a Patient With Semantic Dementia. (September 2014) - Nonaka, Takahiro; Suto, Shunji; Yamakawa, Miyae; Shigenobu, Kazue; Makimoto, Kiyoko
Background: Clock-watching activity in patients with dementia has not been documented in detail. Methods: A male patient having semantic dementia was monitored at a dementia care unit in a general hospital in Japan. We used an integrated circuit monitoring system to record the distance and location of ambulation and the total number of movements that occurred outside the patient's room. Results: The patient was reported to clock watch a couple of years prior to monitoring. In 2011, when monitoring started, he regularly came out of his room saying, "8 o'clock" about 40 minutes into every hour. It seemed as if he could only recognize the minute hand. The median number of sensor detections increased by 4-fold at this clock-watching phase. Behavior consistent with his clock-watching patterns was also detected during the night. In 2012, clock-watching activity disappeared. Conclusions: This study documented the progression of clock-watching and subsequent disappearance with worsening cognitive function.